The role of hydration on the mechanism of allosteric regulation: In situ measurements of the oxygen-linked kinetics of water binding to hemoglobin - Salvay, Andrés Gerardo (2003)
We report here the first direct measurements of changes in protein hydration triggered by a functional binding. This task is achieved by weighing hemoglobin (Hb) and myoglobin films exposed to an atmosphere of 98% relative humidity during oxygenation. The binding of the first oxygen molecules to Hb tetramer triggers a change in protein conformation, which increases binding affinity to the remaining empty sites giving rise to the appearance of cooperative phenomena. Although crystallographic data have evidenced that this structural change increases the protein water-accessible surface area, isobaric osmotic stress experiments in aqueous cosolutions have shown that water binding is linked to Hb oxygenation. Now we show that the differential hydration between fully oxygenated and fully deoxygenated states of these proteins, determined by weighing protein films with a quartz crystal microbalance, agree with the ones determined by osmotic stress in aqueous cosolutions, from the linkage between protein oxygen affinity and water activity. The agreements prove that the changes in water activity brought about by adding osmolytes to the buffer solution shift biochemical equilibrium in proportion to the number of water molecules associated with the reaction. The concomitant kinetics of oxygen and of water binding to Hb have been also determined. The data show that the binding of water molecules to the extra protein surface exposed on the transition from the low-affinity T to the high-affinity R conformations of hemoglobin is the rate-limiting step of Hb cooperative reaction. This evidences that water binding is a crucial step on the allosteric mechanism regulating cooperative interactions, and suggests the possibility that environmental water activity might be engaged in the kinetic control of some important reactions in vivo.